Bidirectional relation between depression and sudden sensorineural hearing loss: Two longitudinal follow-up studies using a national sample cohort - Kim, So Young; Min, Chanyang; Lee, Chang Ho; Park, Bumjung; Choi, Hyo Geun (Scientific reports, 2020)
A few studies have explored the association between depression and sudden sensorineural hearing loss (SSNHL). This study was aimed to investigate the reciprocal relations between SSNHL and depression using a nationwide cohort of the Korean population. Subjects aged > 20 years from the Korean National Health Insurance Service-National Sample Cohort were enrolled from 2002 to 2013. In study I, a total of 60,178 depressed patients were matched 1:4 with 242,872 control I subjects. In study II, a total of 4,328 SSNHL patients were 1:4 matched with 17,312 control II subjects. They were matched for age, sex, income, and region of residence. The Charlson comorbidity index (CCI) was adjusted. Subgroup analysis was performed according to age and sex. The crude and adjusted CCI hazard ratios (HRs) of SSNHL in depressed patients (study I) and depression in SSNHL patients (study II) were analyzed using the stratified Cox proportional-hazard model. In study I, the depression group exhibited an elevated adjusted HR of SSNHL 1.16 times that of the control group (confidence interval [95% CI] = 1.02–1.31, P < 0.023). The middle-aged women subgroup demonstrated an increased risk of SSNHL within the depression group. In study II, the SSNHL group showed a higher adjusted HR of depression 1.29 times that of control II group (95% CI = 1.06–1.57, P = 0.010). The middle-aged women subgroup showed an elevated risk of depression in the SSNHL group. The risk of SSNHL was elevated in the depressed patients and the risk of depression was increased in the SSNHL patients.